Resistance to diseases and pests of tropical pasture plants - Lenné, Jillian M.; Turner, J.W.; Cameron, DF (1980)
In recent years, increasing numbers of pathogens and pests have been reported from major centres of tropical pasture research. Damage is often severe and controls are needed. Diseases and pests may be controlled chemically, biologically, culturally and genetically. In pasture plants genetical resistance is the most practical and economical control method and, as a component of integrated pest management, has considerable potential in controlling pests. Tropical pasture plants have been artificially selected for only a short time. Vast sources of genetic variation exist in their centres of diversity. This natural variation should be utilised in selecting for resistance before initiating long term breeding programmes. Evaluation of resistance to diseases and pests of tropical pasture plants requires understanding of the plant, the pathogen or pest, the environment and their interactions. Primary germplasm evaluation for resistance in plant centres of diversity is strongly recommended and high priority should be given to understanding resistance mechanisms. The importance of multidiscipline collaborative research on resistance to diseases and pests of tropical pasture plants is stressed.